PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PERBANKAN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) PERIODE 2008-2012 (Students' Journal of Accounting and Banking, 2014)
This study aimed to examine the effect of sales growth, profitability, liquidity, and firm size on capital structure on banking companies listed in Indonesia Stock Exchange (IDX) with the perpesctive of trade-off theory models. This study used purposive sampling and obtain a sample of 27 sample companies. Secondary data was obtained through IDX (Indonesian Stock Exchange), the annual report on banking companies listed in Indonesia Stock Exchange (IDX) in 2008-2012. The method of analysis used multiple linear regression analysis to explain the relationship between these variables. The results of this study indicate that all the independent variables simultaneously, namely sales growth, profitability, liquidity and firm size affect the dependent variable is capital structure. Whreas in partial, sales growth and profitability significant positive effect on capital structure, liquidity and firm size variables not significant negative effect on capital structure.Keywords: Sales Growth, Profitability, Liquidity, Firm Size, and Capital Structure